2021
DOI: 10.1007/s00405-021-07172-y
|View full text |Cite
|
Sign up to set email alerts
|

Role and mechanism of Glut-1 and H+/K+-ATPase expression in pepsin-induced development of vocal cord leukoplakia

Abstract: Purpose We investigated the role of Glut-1 and H+/K+-ATPase expression in pepsin-induced development of human vocal cord leukoplakia cells (HVCLCs). Next, we analyzed the relationship between Glut-1 and H+/K+-ATPase expression with the clinicopathological features of laryngeal carcinoma. Methods Glut-1 and H+/K+-ATPase expression levels in HVCLCs were determined after treatment with artificial gastric juice containing pepsin and laryngeal carcinoma tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…The inhibition of GLUT1 expression has been reported to block glycolysis and improve radiosensitivity, and also inhibit cell proliferation and glucose uptake in case of laryngeal cancer [19-21, 40, 41]. Acidified pepsin can increase GLUT1 protein expression in VFL epithelial cells [7]; our findings further validated this observation. GLUT1 upregulation in VFL epithelial cells promoted glucose uptake, lactate secretion, cell activity, S phase ratio, and migration capability, which could be partially blocked by 2-DG.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The inhibition of GLUT1 expression has been reported to block glycolysis and improve radiosensitivity, and also inhibit cell proliferation and glucose uptake in case of laryngeal cancer [19-21, 40, 41]. Acidified pepsin can increase GLUT1 protein expression in VFL epithelial cells [7]; our findings further validated this observation. GLUT1 upregulation in VFL epithelial cells promoted glucose uptake, lactate secretion, cell activity, S phase ratio, and migration capability, which could be partially blocked by 2-DG.…”
Section: Discussionsupporting
confidence: 86%
“…Laryngopharyngeal reflux (LPR) evidently plays a key role in VFL development and malignant transformation [ 7 , 8 ]. LPR contents include gastric acid as well as non-acid components.…”
Section: Introductionmentioning
confidence: 99%
“…We earlier reported high pepsin levels in vocal cord polyps and patients with vocal cord leukoplakia [5]; the latter expression level increased significantly as the dysplasia grade rose [5]. We also found that high Glut-1 expression may improve the development of vocal cord leukoplakia by upregulating laryngeal H + /K + -ATPase expression to reactivate absorbed pepsin resulting in laryngeal mucosa injury in vitro [6]. There is the same mechanism of pepsin-mediated tissue damage in vivo is unclear.…”
Section: Introductionmentioning
confidence: 76%
“…Esophageal mucosal epithelial injury is caused principally by gastric acid secreted by the proton pump H + /K + -ATPase [3]; pepsin damages the laryngopharyngeal epithelium [4,5]. Pepsin is abnormally expressed in patients with voice disorders, vocal cord polyps, laryngeal stenosis, vocal cord leukoplakia, and malignant lesions [5,6]. We earlier reported high pepsin levels in vocal cord polyps and patients with vocal cord leukoplakia [5]; the latter expression level increased significantly as the dysplasia grade rose [5].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying etiologies for the development of leukoplakia patches or plaques are long-term smoking and alcohol abuse, inhaled irritant substances, and viral infections such as HPV [ 12 ]. Other possible etiological factors are occupational hazards, nutritional deficiencies, vocal misuse/abuse, chronic infections, hormonal disorders, and laryngopharyngeal reflux disease [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%